Static vulnerability of an existing r.c. structure and seismic retrofitting by CFRP and base-isolation: A case study. Issue 84 (May 2016) - Mazza, Fabio; Pucci, Daniela
Abstract: The assessment of the static vulnerability under gravity loads of existing reinforced concrete (r.c.) framed buildings is a serious problem that requires the use of reliable methodologies to evaluate ductile and brittle mechanisms. The present work compares alternative formulations of member chord rotation and section and joint shear strength, proposed by Italian and European seismic codes and guidelines and other expressions available in the scientific literature. To this end, a r.c. framed building built sixty years ago with bi-directional (perimeter) and mono-directional (interior) plane frames, originally designed for five storeys then elevated to six during construction, is studied. A full characterization of the structure and its materials is carried out by means of destructive and non-destructive methods. Then, retrofitting based on the use of both innovative material, such as carbon fibre reinforced polymers (CFRP), and technology, such as base-isolation, are adopted to improve the static and seismic performances of the original structure. Finally, nonlinear analyses are carried out on a three-dimensional fibre model of the original and retrofitted structures, where an elastic linear law idealizes the behaviour of the CFRP up to tension failure and viscoelastic linear and bilinear models are used to idealize the behaviour of the elastomeric and sliding bearings, respectively. Highlights: Comparison of alternative formulations of member chord rotation. Comparison of alternative formulations of section shear strength. Comparison of alternative formulations of joint shear strength. Static vulnerability of fixed-base structures with and without CFRP strengthening. Seismic retrofitting with base-isolation acting alone or in combination with CFRP.